The Effect of Problem Based Learning (PBL) Based on Local Wisdom in Making Lemang Kancung Beruk on Students' Critical Thinking Skills - Sri Anika Cahayu; Jodion Siburian; Afreni Hamidah (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to determine how the effect of local wisdom- based PBL model on making Lemang Kancung Beruk on critical thinking skills. The research method is a quasi-experimental form of non-equivalent pretest-posttest control group design with purposive sampling technique. The research population was Phase D of SMP Negeri 6 Sungai Penuh, the research sample was class VII A and VII B with a total of 36 students, 18 students each from class VII A as the experimental class and class VII B as the control class. Data collection techniques used FRISCO indicator critical thinking ability essay tests and observation sheets. Data analysis technique used one-way Ancova test with initial critical thinking ability as covariate. The results showed that the average value of the experimental class posttest results was higher at 88.19 than the control class 70.60. The hypothesis test results obtained the value [F (1.33) = 49.515, p < 0.001, ηp2 = 0.600] showing the significance of p < 0.001 which means < 0.05, meaning that there is an effect of the local wisdom-based PBL model on making Lemang Kancung Beruk with an effect size value of ηp2 = 0.600 has a large effect.